Effects of different educational interventions on cervical cancer knowledge and human papillomavirus vaccination uptake among young women in Japan: Preliminary results of a cluster randomized controlled trial. - Yuko Takahashi; Yukifumi Sasamori; Risa Higuchi; Asumi Kaku; Tomoo Kumagai; Saya Watanabe; Miki Nishizawa; Kazuki Takasaki; Haruka Nishida; Takayuki Ichinose; Mana Hirano; Yuko Miyagawa; et al. (PLoS ONE)
The incidence and mortality rates of cervical cancer are increasing among young Japanese women. In November 2021, the Japanese Ministry of Health, Labour, and Welfare reinstated the active recommendation of the human papillomavirus (HPV) vaccine, after it had been suspended in June 2013 due to reports of adverse reactions. However, vaccine hesitancy is prevalent in the younger generation in Japan. To identify obstacles to vaccine uptake, we conducted a randomized study using different methods to provide educational content to improve health literacy regarding cervical cancer and HPV vaccination among Japanese female students. We surveyed 188 Japanese female students, divided into three groups according to the intervention: no intervention, print-based intervention, and social networking service-based intervention. Twenty questionnaires and the Communicative and Critical Health Literacy scales were used as health literacy scales. Participants' knowledge and health literacy improved regardless of the method of education. In fact, participants acquired proper knowledge when given the opportunity to learn about the importance of the disease and its prevention. Therefore, medical professionals in Japan must provide accurate scientific knowledge regarding routine HPV vaccination and the risk of cervical cancer in young women to improve their health literacy and subsequently increase HPV vaccination rates in Japan, which may lead to cervical cancer elimination. Trial registration number: UMIN000036636.